Charles Taylor and Liberia : ambition and atrocity in Africa's Lone Star State - Waugh, Colin M., 1955- (London, England ; New York, NY : Zed Books, 2011)
Campaigner, insurgent, arms dealer, warlord, commodity trafficker, elected president, international fugitive, and finally prisoner, Charles Taylor sought to lead his native Liberia to change but instead destroyed it in a frenzy of violence, greed, and uncontrolled personal ambition. In the process, he threw much of Liberia's neighboring region into turmoil for over a decade, finally facing judgment in The Hague for his role in the Sierra Leone conflict. In this book, Colin Waugh examines both the life of Taylor himself, as well as the sometimes idealistic but often self-interested efforts of the international community to first save Liberia and the region from disaster, then, having failed to do so, to bring to justice the man it deems most to blame for the turmoil.
Foundations of a settlement -- Spirit of Liberia -- Confronting the old order -- Sergeant-in-charge: Samuel Doe's presidency -- Doe's decline, Taylor's travels -- Charles Taylor's war -- Pantomime of peace -- Greater Liberia: prospering and assimilating -- Sierra Leone: Liberia's sister revolution -- Election victory and the Taylor presidency -- Government embattled -- Relations with the United States -- Liberian legacy -- Justice a la carte.
Includes bibliographical references (pages 360-363) and index.
Keywords: Taylor, Charles Ghankay; Since 1980; Presidents -- Liberia -- Biography; Liberia -- History -- Civil War, 1989-1996.; Liberia -- History -- Civil War, 1999-2003.; Liberia -- Politics and government -- 1980-; Biographies